2014
DOI: 10.1177/0748730414533289
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Masking and cFos Responses to Light in Day- and Night-Active Grass Rats

Abstract: Light not only entrains the circadian system but also has acute effects on physiology and behavior, a phenomenon known as masking. Behavioral masking responses to bright light differ in diurnal and nocturnal species, such that light increases arousal in the former and decreases it in the latter. Comparisons made within a species that displays both diurnal and nocturnal patterns of behavior may provide insight into how masking differs between chronotypes and the association between mechanisms controlling maskin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…As recently shown in a mice study, light induces c-Fos activation in some brain areas such as LHb, but not in others such as DLG (dorsal lateral geniculate), where light rather cause a decrease of c-Fos activation [65]. It was reported that light does not induce changes in c-Fos in retinorecipient areas such as in the LHb, dorsal lateral geniculate (DGL), in the ventral subparalventricular zone (vSPZ), suprachiasmic nucleus (SCN) or in the VLGMC of night active grass rats [65, 66]. Our data are in accordance with other previous studies showing that CMS animals display circadian rhythm disturbances [67] which are common symptoms of MDD [68].…”
Section: Discussionmentioning
confidence: 99%
“…As recently shown in a mice study, light induces c-Fos activation in some brain areas such as LHb, but not in others such as DLG (dorsal lateral geniculate), where light rather cause a decrease of c-Fos activation [65]. It was reported that light does not induce changes in c-Fos in retinorecipient areas such as in the LHb, dorsal lateral geniculate (DGL), in the ventral subparalventricular zone (vSPZ), suprachiasmic nucleus (SCN) or in the VLGMC of night active grass rats [65, 66]. Our data are in accordance with other previous studies showing that CMS animals display circadian rhythm disturbances [67] which are common symptoms of MDD [68].…”
Section: Discussionmentioning
confidence: 99%
“…The OPT is retinorecipient [8], reciprocally connected to the IGL [4,9], and exhibits a Fos response to light [13,24]. The OPT mediates pupillary reflexes to light and is involved in the generation of eye movements [25], but may also be involved in sleep and circadian behavior [10,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…For example, for grass rats that become night-active when given a running wheel, the OPT does not exhibit light-induced Fos at ZT14, whereas it does so in day-active wheel-runners [24]. Also, light induces Fos in the OPT of intact grass rats, but decreases it in intact mice [28]; this result stands in contrast to findings in laboratory rats [13], in which 2-h light pulses given at ZT19 induce increased Fos-ir in the OPT.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that generalizations about the effects of light on sleep or arousal that are deduced from studies of nocturnal species may not apply to diurnal animals (for discussion, see Shuboni et al, 2012 ; Langel et al, 2014 ). In humans, for example, nocturnal light enhances alertness (for review, see Cajochen, 2007 ; Hubbard et al, 2013 ), contrary to the effects observed in small nocturnal laboratory rodents.…”
Section: Photic Modification Of Sleep In Nocturnal Rodentsmentioning
confidence: 99%